2014
DOI: 10.3390/e16052629
|View full text |Cite
|
Sign up to set email alerts
|

Using Neighbor Diversity to Detect Fraudsters in Online Auctions

Abstract: Online auctions attract not only legitimate businesses trying to sell their products but also fraudsters wishing to commit fraudulent transactions. Consequently, fraudster detection is crucial to ensure the continued success of online auctions. This paper proposes an approach to detect fraudsters based on the concept of neighbor diversity. The neighbor diversity of an auction account quantifies the diversity of all traders that have transactions with this account. Based on four different features of each trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Therefore, several studies have focused on detecting cohesive groups in social networks [3][4][5][6]. By contrast, a recent study [7] suggested that the neighbors of a fraudster in a social network exhibit similar behavior leading to low neighbor diversity. Thus, the concept of neighbor diversity was proposed for fraudster detection.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, several studies have focused on detecting cohesive groups in social networks [3][4][5][6]. By contrast, a recent study [7] suggested that the neighbors of a fraudster in a social network exhibit similar behavior leading to low neighbor diversity. Thus, the concept of neighbor diversity was proposed for fraudster detection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the center weight improves the precision of fraudster detection, it reduces the recall [4]. Lin and Khomnotai [7] suggested that the neighbors of fraudsters in social networks exhibit similar patterns because fraudsters need their collusive neighbors to give them positive ratings in the reputation system. Thus, the concept of neighbor diversity was proposed for fraudster detection, where nodes with low neighbor diversity are likely to be fraudsters.…”
Section: Sna Featuresmentioning
confidence: 99%
See 3 more Smart Citations